2019
DOI: 10.1590/s0100-83582019370100145
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate Resistance Affect the Physiological Quality of Conyza bonariensis seeds

Abstract: High seed production and dispersal capacity and glyphosate resistance are among the main factors that have made hairy fleabane (Conyza bonariensis) one of the most important and dispersed weeds in the world. Herbicide-resistant weeds populations may have fitness cost due to molecular, physiological, and biochemical changes. This study aimed to evaluate the physiological quality of seeds of Conyza spp. and determine whether glyphosate resistance causes fitness costs for resistant biotypes. Seeds from six hairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…sumatrensis by its leaves, stems, and involucres being glabrous or subglabrous (vs. moderately to largely pilose) (Figure 4). We did not find C. blakei and C. canadensis among the 314 plants from 20 accessions (fields) across Brazil, although they were reported in field crops in the country (Piasecki et al 2019;Vidal et al 2007). Conyza blakei differs from C. bonariensis and C. sumatrensis by its pinnatisect lower leaves (vs. linear or obovate) and narrow capitulescence (vs. moderately elongated) (Sancho 2014).…”
Section: Species Identification Through Morphologycontrasting
confidence: 61%
“…sumatrensis by its leaves, stems, and involucres being glabrous or subglabrous (vs. moderately to largely pilose) (Figure 4). We did not find C. blakei and C. canadensis among the 314 plants from 20 accessions (fields) across Brazil, although they were reported in field crops in the country (Piasecki et al 2019;Vidal et al 2007). Conyza blakei differs from C. bonariensis and C. sumatrensis by its pinnatisect lower leaves (vs. linear or obovate) and narrow capitulescence (vs. moderately elongated) (Sancho 2014).…”
Section: Species Identification Through Morphologycontrasting
confidence: 61%
“…In addition, the GR 50 values of the S populations, regardless of the different geographic origins of each biotype, were similar. Piasecki et al [18] observed a similar phenomenon, with S populations of C. bonariensis collected in different regions of southern Brazil showing no differences in their GR 50 (also less than 100 g ae ha −1 ). The R biotypes, in turn, presented different GR 50 values, revealing different profiles of glyphosate resistance; however, the GR 80 values were below the field dose recommended by the manufacturer for this species (960 g ae ha −1 ), except for biotype R1 (GR 80 = 1.030 g ha −1 ).…”
Section: Discussionmentioning
confidence: 62%
“…At the vegetative level, there is no evidence for fitness cost in glyphosate-resistant Conyza species [5,26,28,37]; however, our results suggest that there may be a seed level fitness penalty in C. bonariensis. Piasecki et al [18] also observed a reduction in the vigor and germination rate in seeds of glyphosate-resistant Conyza species and, in turn, a significant increase in both empty and dormant seeds. In addition, glyphosate application at the vegetative and reproductive stages impairs the production and viability of glyphosate-resistant C. bonariensis seeds [29].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the superior root length presented by the resistant biotype provides rapid growth of the roots, and can confer a competitive advantage in cases in which interactions below ground predominate (SEIBERT; PEARCE, 1993). However, in a similar study, Piasecki et al (2019) observed a reduction in the physiological quality of glyphosate-resistant C. bonariensis seeds, demonstrating a possible effect of the origin of the biotypes on the physiological capacity of the seeds.…”
Section: Physiological Potential Of Seeds and Spread Of Herbicide Resistancementioning
confidence: 73%